A cross sectional study to determine the knowledge and practices of Pap smear test among women - M. Indira; N. Sangeetha; P. Kasi Krishna Raja; A. K. Choudhary; K. Sharma (ABV-press, 2022)
Cervical cancer is the second most common malignancy among Indian women. Every year, 122844 women are diagnosed with cervical cancer, with 67477 dying as a result of it. It primarily affects women between the ages of 15 and 44 who are in the reproductive age group1. This is primarily due to a delay in early cervical pathology diagnosis and treatment. From September 2017 to February 2018, a descriptive cross-sectional study was undertaken in the Obstetrics and Gynecology OPD at Govt. Erode Medical College, Perundurai, Erode District, Tamilnadu women ≥20 years age visiting Obstetrics and Gynecology OPD. The majority of women, 84.4 percent, married after they turned 18 years old (211). And 15.6 percent of the population was under the age of 18. Hinduism was followed by 97.2 percent, Christians by 1.6 percent, and Muslims by 1.2 percent. Doctors were the source of information for 36.3 % of those in our survey, while health workers educated 26 %. 25.9 % got their knowledge from the media, while 14 % got it from relatives and friends. According to our research, the most common reasons for refusing a Pap smear are dread of having to undergo a test (46.7 %) and a delay in receiving the results. When people are asymptomatic and have already been screened, 23 % believe it is unnecessary to go through the process again. They were not ready to acknowledge the requirement for pre-programmed serial screening.The importance of immunization and the role of the vaccine for the human papillomavirus must also be educated. Given the main reason given by the participants for not having the test, it is critical that all health providers use every opportunity they have with women to educate and encourage them to do so.